Adaptasi Perancangan Interior Supermarket di Masa Pandemi Covid-19 sebagai Upaya Reduksi Tingkat Kerumunan - Boelhasrin, Afina Fakhrini; Wibisono, Andriyanto (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2023)
Covid-19 pandemic that occurred in 2019 spread to the world, including Indonesia as a country. Pembatasan Sosial Berskala Besar (PSBB) as one of the efforts to overcome the problem by Indonesian government forced all public facilities to limit activities inside. However, supermarket is one of the public facilities that must remain open to fulfill basic needs of the community, which increases supermarket crowding level and potential to become a place for virus transmission. The purpose of this research is to analyze design adaptation of supermarket to respond Covid-19 Pandemic with crowing indicator as the main consideration. The research method used at the data collection stage was online questionnaire to specify the research area, the result of data collection then being analyzed with descriptive qualitative method to produce design adaptation recommendation alongside supporting theories. The research is conducted in basic needs display area that has higher risk of virus transmission. The research resulting design adaptation recommendation which are application of middle aisle layout, re-layout of display area, and circulation patterns adaptation.